2010
DOI: 10.1093/jb/mvq114
|View full text |Cite
|
Sign up to set email alerts
|

Autocrine TGF-β protects breast cancer cells from apoptosis through reduction of BH3-only protein, Bim

Abstract: Cancer cells undergo multi-step processes in obtaining the ability to metastasize, and are constantly exposed to signals that induce apoptosis. Acquisition of anti-apoptotic properties by cancer cells is important for metastasis, and recent studies suggest that transforming growth factor (TGF)-β promotes the survival of certain types of cancer cells. Here, we found that in highly metastatic breast cancer cells, JygMC(A), JygMC(B) and 4T1, TGF-β ligands were produced in autocrine fashion. Pharmacological inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 47 publications
4
42
0
1
Order By: Relevance
“…5B). Similar to previous reports (12,(20)(21)(22), TGF-β signaling was enhanced upon TGF-β2 treatment, indicating a functional TGF-β pathway in 4T1 cells. Conversely, inhibition of TGF-β signaling dramatically decreased phosphorylation of Akt and Twist1 (Fig.…”
supporting
confidence: 91%
“…5B). Similar to previous reports (12,(20)(21)(22), TGF-β signaling was enhanced upon TGF-β2 treatment, indicating a functional TGF-β pathway in 4T1 cells. Conversely, inhibition of TGF-β signaling dramatically decreased phosphorylation of Akt and Twist1 (Fig.…”
supporting
confidence: 91%
“…Apart from its roles in EMT induction, TGFb has also been implicated in the ability of cancers to avoid conventional apoptotic pathways. In one such recent study, TGFb has been shown to protect breast cancer cells through a FOXC1-dependent mechanism through regulation of the pro-apoptotic protein bim (Hoshino et al, 2011). It is likely, therefore, that the contribution of FOXC1 to the aggressive phenotypes associated with BLBC may occur through several cooperating mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative real-time RT-PCR (qRT-PCR) analysis and chromatin immunoprecipitation (ChIP)-qRT-PCR analysis were performed as previously described (7,8). Primer sequences are described in Supplementary Table S1.…”
Section: Quantitative Real-time Rt-pcr Analyses and Chromatin Immunopmentioning
confidence: 99%
“…Terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) assay was performed as previously described (7). Fluorescence was examined using a Leica DMI6000 B.…”
Section: Apoptosis Assaymentioning
confidence: 99%